Changes in living from the child / adolescent diagnosis with HIV/AIDS and facilities found in care (Research, Society and Development, 2020)
Objective: The presented research aims to know the changes in living from the diagnosis of the child/adolescent with HIV/AIDS and facilities in the exercised care. Methodology: Descriptive, exploratory and qualitative carried out in southern Brazil in 2018. Participated 20 family caregivers of HIV-positive children/adolescents. Data were collected through interviews and submitted to Content Analysis. Ethical principles were respected. Results: About changes, it was found that the family caregiver starts to dedicate themselves exclusively to care, they are concerned that only the nuclear family is dedicated to the care of the child/adolescent. They reported that the disease served to unite the familyand that there was a change in diet. Concerning the facilities, on the other hand, reported not having difficulties, as the child/adolescent does not bother, accepts all the care and routines proposed for their well-being. They stated that they have a life like that of any other child/adolescent, and have no difficulties. They mentioned that the child/adolescent accepts his diagnosis and does not suffer prejudice. They also referred obtaining a judicial benefit by giving them more time to care for the child. Conclusion: the importance of constant nursing work with families is perceived through health education and guidance, to instruct and prepare them to deal with existing routines and adversities.